Qualified Conservation Restrictions: Recollections of and Reflections on the Origins of Section 170(h) (Utah Environmental Law Review; Vol 33 No 1 (2013), 2014)
It has been over thirty years since Congress added to the Internal Revenue Code section 170(h), which allows a deduction for contributions to charity of “qualified conservation restrictions,” commonly known as “conservation easements”. That provision was adopted over the objections of the Treasury, who had expressed reservations of both a conceptual and practical nature about the legislation, which the Treasury viewed as more than ordinarily vulnerable to abuse. I was invited to participate in this symposium, not because I have any expertise in working with these restrictions—I don’t—but to provide some perspective on what might have motivated the Treasury thirty-plus years ago to take the position that it did, on what is very popular legislation among the conservation and historic preservation communities. I think of myself as no better than the second most qualified individual to fill that role. The most qualified, in my opinion, is Professor Daniel Halperin, who served as the Deputy Assistant Secretary for Tax Policy when the legislation was under deliberation, testified twice on versions of the proposed legislation, and has recently written in this area.3 But I was there at the time; I did work with Professor Halperin on his testimony and the legislation; and so I am able to offer a (sometimes more and sometimes less vaguely recalled) first-hand account of what was happening then. In some respects I find it advantageous not to have worked in this area in the intervening years. The invitation to participate in this symposium offered me an opportunity to reflect on whether I think the positions the Treasury took then rested on well-founded concerns, and to speculate on whether, if I had known then what I have learned since, I would have recommended that the Treasury approach the matter in exactly the fashion that it did.